Long Non-Coding RNA CCAT2 Promotes the Development of Esophageal Squamous Cell Carcinoma by Inhibiting miR-200b to Upregulate the IGF2BP2/TK1 Axis - Wu, Xiaodan; Fan, Yihui; Liu, Yupeng; Shen, Biao; Lu, Haimin; Ma, Haitao (Frontiers in Oncology, 2021)
Long non-coding RNAs (lncRNAs) have been shown to play important roles in human cancers, including esophageal squamous cell carcinoma (ESCC). In the current study, we identified CCAT2 as a relevant lncRNA and investigated its role in the progression of ESCC. RT-qPCR was adopted to detect CCAT2 expression in collected clinical samples, ESCC cell lines, and a normal cell line. We tested the correlation between CCAT2 expression and the prognosis of ESCC. RT-qPCR or immunoblotting was adopted to detect the expression of relevant factors in ESCC tissues or cells. Cell proliferation, apoptosis, migration, and invasion were examined by colony formation assay, flow cytometry, scratch assay, and Transwell assay, respectively, while subcutaneous tumorigenesis in nude mice was adopted to examine the role of CCAT2 in tumorigenesis of ESCC cells in vivo. Bioinformatics analysis, dual luciferase reporter assay, and RIP were conducted for the target relationship profiling. Me-RIP was adopted to detect m6A modification level of TK1 in ESCC tissues or cells. Upregulated CCAT2, IGF2BP2, and TK1 expression and inhibited miR-200b expression were observed in ESCC cells and tissues. CCAT2 bound to miR-200b and reduced its expression, leading to upregulated IGF2BP2 expression. IGF2BP2 improved TK1 mRNA stability to enhance its expression by recognizing its m6A modification. CCAT2 promoted the migration and invasion of ESCC cells in vitro, and tumorigenesis in vivo by upregulating TK1 expression, while overexpression of miR-200b reversed these effects of CCAT2. Overall, this study suggests that CCAT2 competitively binds to miR-200b to alleviate its inhibitory effects on IGF2BP2 expression, resulting in elevated TK1 expression, and an ensuing promotion of the development of ESCC.